Level of physical and emotional implications for nurse medical indication versus withdrawal of life support methods in the terminal patient, the Intensive Care Unit “National Maternal Perinatal Institute” and the “Central Hospital of the Air Force of Peru - Espinoza de la Sota, Irene Beatriz (2019)
Objective: To determine the level of physical and emotional implications of the nursing professional medicaladvice against removal of life-sustaining terminal patient in the Intensive Care National Maternal PerinatalInstitute and the Central Hospital of the Air Force Peru . Methodology: The study design was observational,descriptive, cross-sectional. The sample was universal, it consisted of the 30 nurses comprised of intensive careunits who participated voluntarily population. As an instrument, a questionnaire developed by the researchers,validated by expert judgment, which allowed us to collect specific data to assess the level of physical andemotional implications nursing professionals was used. Results: The results were: 67 % of nurses presented a lowlevel of physical implications and 16.5 % a moderate level; 50% had a high level of high emotional implicationsand 40% a moderate level. Conclusions: The indication of withdrawal of life support methods in the terminalpatient ICU had a higher level of emotional implications and a lower level of physical implications for nurses.